315 Incidence of Infections in Full-Endoscopic Spine Surgery: A Multicenter Study Including 1262 Patients. (1st April 2022) - Prasse, Tobias; Wagner, Ralf; Mahan, Mark A.; Kim, Robert; Sivakanthan, Sananthan; Telfeian, Albert E.; Bergquist, Julia; Bredow, Jan; Kashlan, Osama; Hofstetter, Christoph P.
Abstract : INTRODUCTION: Full-endoscopic spine surgery (FESS) is a rapidly growing field. There is emerging class I data that it results in equal or better functional outcomes compared to traditional surgery while minimizing approach related morbidity and perioperative complications. METHODS: 569 women (45.1%) and 693 men (54.9%) were identified in our prospectively collected cohort at two different spine centers. Demographic data, complications in particular occurrence of infections was analyzed. The Charlson Comorbidity Index was used to quantify the comorbidities in relation to the patients' age by predicting the 10-year survival. RESULTS: The average age of the patients was 56.6 years (±15.5), 100 cases were cervical (7.9%), 24 thoracic (1.9%) and 1138 lumbosacral (90.2%). The mean Charlson Comorbidity Index was 1.95 (±1.8). 68 patients (5.4%) took immunosuppressive drugs. 21 complications were found in 1262 cases (1.7%). None of our patients had a superficial or deep wound infection. Eight patients had dural tears (0.6%), of which one presented as a cutaneous fistula with delayed wound healing. Bacterial cultures and DNA tests were negative, there were no clinical signs for infection and the patient did not need revision surgery, but was treated by lumbar drain placement. Postoperatively, 3 epidural hematomas (0.2%), 2 transient ischemic attacks (0.2%), 2 hypertensive crises (0.2%) and one myocardial infarction (0.08%) were observed. Only 5 (0.4%) of the patients had a recurrent disc herniation. CONCLUSION: Full-endoscopic spine surgery is associated with a favorably low rate of wound-related complications such as infections or dehiscence. We hypothesize this is due to coverage of the skin edge by the tubular retractor avoiding spreading skin flora into the surgical area as well as constant irrigation of the operative field. Low rate of adverse outcomes strongly supports utilization of this technique when indicated.